RANCANG BANGUN PEMBANGKIT LISTRIK TURBIN AIR MIKRO HIDRO TIPE CROSS-FLOW KAPASITAS 2.500 WATT DI KP. MULYASARI -BOGOR JAWA BARAT - Azharul, Firmansyah; Dharmanto, Asep; Wilarso, Wilarso (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2020)
To meet the electricity needs at night and the production of agricultural products in Kp. Mulyasari was designed and built a Micro Hydro Power Plant (PLTMH) Turbine which can produce power up to 2,500 Watt. This machine is designed to be easy to install, easy to operate, inexpensive to maintain. The selected turbine type is a Cross-Flow air turbine for a low head. Turbines operate at impulse pressure, where the potential energy of water is converted into kinetic energy through the nozzles to push the turbine's front blades. In the design of this turbine, it is designed, so that it has a long life span, low investment value, minimal maintenance costs, easy installation costs, and is driven by water, thereby conserving natural resources. The turbine is designed based on data from field survey results in Kp. Mulyasari, with results; Head (H) = 1.85 m; Water discharge (Q) = 0.2 m3 / s; Turbine rotation (planned) (n) = 214 rpm; Turbine efficiency (plan) (?t) = 68%; Density of water (?) = 997.8 kg / m3. From the calculation results, obtained the Cross-Flow turbine design specifications as follows: High waterfall (H) = 1.85 m; Water discharge (Q) = 0.2 m3 / s; Turbine efficiency (plan) (?t) = 68%; Power (N) = 2,497 kW; Rotation (n) = 214 rpm; Specific speed (ns) = 770,4138831 rpm; Road blade diameter (DL) = 0.40 m; Naaf diameter (Dn) = 0.035 m; Steering blade width (B) = 0.032 m; Number of road blades = 26 pieces.